Repair of Perineal Hernia Following Abdominoperineal Excision with Biological Mesh: A Systematic Review - Narang, Sunil K.; Alam, Nasra N.; Köckerling, Ferdinand; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2016)
Introduction Perineal hernia (PerH) following abdominoperineal excision (APE) procedure is a recognised complication. PerH was considered an infrequent complication of abdominoperineal excision procedure, however, PerH rates of up to 45% have been reported in recent publications following a laparoscopic APE procedure. Various methods of repair of PerH with the use of synthetic meshes or myocutaneous flap have been described although there is no general agreement on an optimal strategy. The use of biological meshes for different operations is growing in popularity and these have been promoted as being superior and safer when compared to synthetic meshes. Although the use of biologics is becoming popular claims of a better outcomes are largely unsupported by evidence. The aim of this systematic review is to evaluate the currently available evidence supporting the use of biologic or biosynthetic meshes for the repair of PerH that develop following an abdominoperineal excision. Methods A systematic review of all English language literature relevant to repair of perineal hernia following abdominoperineal excision with biologic or biosynthetic mesh published between 1st January 2000 and 31st July 2016 was carried out using MEDLINE, EMBASE and the Cochrane Library of Systematic Reviews for relevant literature. Searches were performed using a combination of Medical Subject Headings (MeSH) terms and text words ‘perineal hernia’, ‘abdominoperineal excision’, ‘morbidity’, ‘biologics’, ‘biosynthetic’, and ‘hernia’. Studies in which the use of biological meshes was not reported were excluded from the review. Various outcome measures including operative technique, complication rates, recurrence rates, type of mesh, management of recurrences and risk factors were extracted. Oxford Centre for Evidence-based Medicine – Levels of Evidence (March 2009) was used to assess the quality of evidence Results The systematic review of the literature identified 3 case reports, 4 case series and 1 pooled analysis that were included in the final review. Overall these studies were of poor quality providing level 4 evidence. Various different approaches and techniques of repair of PerH were described, however, it was difficult to extract information with regards to the primary and secondary outcome measures. Conclusions There is no general agreement to the optimal operative strategy to repair